Proton pump inhibitor (PPI) administration and Clostridioides difficile infection - is this a real clinical problem? A critical review of the literature - Głaz, Aneta; Knop, Kinga; Kochanowska, Anna; Wach, Damian; Piasecka, Zuzanna; Wesołek, Ewelina; Kasztelan-Szczerbińska, Beata; Skrzydło-Radomańska, Barbara (Journal of Education, Health and Sport, 2023)
Background: Proton pump inhibitors (PPIs) are widely used drugs that reduce gastric acid secretion. In recent years, there has been a gradual increase in their use. The safety of prolonged PPI therapy and the potential for cumulative side effects of these drugs raise legitimate concerns. An association between PPI administration and the risk of Clostridioides difficile infection has been suggested. The findings regarding this phenomenon require further unequivocal verification. Material and methods: A review of publications obtained from the PubMed database and published between 2016-2023. Based on the keywords "proton pump inhibitor", "PPI" and "Clostridium", 132 articles were selected. Finally, 6 meta-analyses were included in the analysis. Results: Studies conducted in recent years have shown a statistically significant increase in the risk of C. difficile infection in patients taking PPIs compared to those who avoid this therapy. The aforementioned relationship was observed in both adults and pediatric patients. One study proved that the risk remained high even up to 1 year after the end of treatment. The described relationship is still a matter of debate due to the fact that patients using antacids are usually elderly, have several comorbidities and a higher risk of developing C. difficile infection regardless of PPI use. Conclusions: The relationship between the use of PPIs and the risk of developing C. difficile infection is still controversial, which justifies the need for continued clinical trials to objectively resolve this issue. PPIs exert high efficacy in the treatment of acid-dependent diseases, but due to the many ambiguities surrounding possible side effects, caution in their administration seems warranted, especially for long-term therapy in elderly patients with polypharmacy.